FROM ONLINE ENGAGEMENT TO OFFLINE ACTIONS: UNDERSTANDING THE IMPACT OF CANCER (MIS)INFORMATION ENGAGEMENT AMONG LATINO FACEBOOK USERS - Rivera, Yonaira M (AoIR Selected Papers of Internet Research, 2020)
Latinos in the U.S. face a high burden of cancer, making it important to deliver evidence-based cancer prevention and screening information (CPSI) on social media to this group. However, there is a dearth in scholarship exploring how Latinos engage with and act upon cancer (mis)information encountered on social media. Cultural values may influence how Latinos engage with multi-lingual CPSI shared on Facebook. This study sought to understand how and why U.S. Latinos engage with and act upon CPSI on Facebook. During one-on-one, in-depth interviews, participants (n=20) logged onto their Facebook account alongside the researcher, typed “cancer” in the search bar, and discussed CPSI they engaged with during the past 12 months. Engagement prompted questions regarding the reasons for engagement and further action. Computer screen and audio were recorded. Interviews were analyzed thematically; CPSI was analyzed via content analysis. Participants mainly engaged with CPSI by viewing/reading content. Engagement was most common when individuals had personal relationships to the poster, when posts included videos/images, and when information promoted popular Latin American foods. Engagement often led to varying levels of action, both online and offline. Not all decisions were evidence-based, and some were potentially harmful (e.g. canceling mammogram after engaging with misinformation). Findings highlight the complex and interrelated ways in which cultural values, source factors and message factors contribute to engagement with health content on social media, which may lead individuals to bypass evidence-based procedures in favor of unproven approaches. Specific interdisciplinary recommendations to address these issues will be discussed.